Phytochemical profiling of Vitex negundo seeds via UHPLC-QTOF-MS/MS analyses with antimicrobial evaluation and in silico targeting of DNA Gyrase B and Secreted Aspartic Proteinase 2 (SAP2) - Javed Mustafa; Tuba Ashraf; Basharat Ali; Shazia Kousar; Adeem Mahmood; Saif Ullah; Muhammad Imran; Bakhat Ali; Usman Rahim; Muhammad Yunis (PLoS ONE, 2026)
The present study reports the metabolic profiling and antimicrobial evaluation of Vitex negundo seed extract. UHPLC-QTOF-MS/MS analysis identified seventeen bioactive phytoconstituents, correlated with the observed antimicrobial and antifungal activities. Among them, isoorientin (–7.3 kcal mol ⁻ ¹), quercetin (–7.8 kcal mol ⁻ ¹), and orientin (–7.4 kcal mol ⁻ ¹) exhibited strong binding affinities towards Staph Gyrase B (24 kDa). Similarly, isoorientin (–8.1 kcal mol ⁻ ¹), quercetin (–8.4 kcal mol ⁻ ¹), and orientin (–8.3 kcal mol ⁻ ¹) displayed significant interactions with secreted aspartic proteinase (SAP2) enzyme, confirming their antimicrobial potential. The aqueous-methanolic seed extract demonstrated notable inhibitory activity against Staphylococcus aureus (26.4 ± 0.3 mm; 44.08% inhibition) and Candida albicans (25.7 ± 0.4 mm; 29.73% inhibition). Density functional theory (DFT) calculations at B3LYP/6-31G level were used to optimize the ground state geometries of the identified phytochemicals and analyze their frontier molecular orbitals (FMOs) and global reactivity descriptors. Time-dependent DFT (TDDFT) calculations at the B3LYP/6-311G level (solvent: DMSO) further explored their biological relevance and nonlinear optical (NLO) properties, including ionization potential (IP), molecular electrostatic potential (MEP), and HOMO-LUMO energy gaps. These quantum chemical parameters provided mechanistic insights into the antimicrobial potential of the identified constituents. Molecular docking simulations further confirmed strong geometric complementarity and favorable binding affinities, highlighting the Vitex negundo seed extract as a promising source of a novel medicinal agent with previously unreported antifungal and antibacterial activities.